Metodologia alternativa para o teste de frio em sementes de milho - Marques, Fernanda Sedrez (2023)
Maize is one of the most widely grown agricultural products in the world and is of great importance in Brazil's production chain, driving the national and international economy. The cold test is one of the oldest and most popular tests for assessing seed vigor. The aim of this study was to compare methodological procedures for conducting the cold test on maize seeds. The experiment was carried out at the Didactic Laboratory for Seed Analysis (LDAS) of the Graduate Program in Seed Science and Technology at the Federal University of Pelotas. Sixteen batches of maize seeds were used, from the 2021 harvest, with different levels of germination. Initially, the batches were homogenized and the initial characterization of the batches was carried out using the water content, germination and seedling emergence tests. The adapted cold test methodology was then carried out, using Germitest® paper as a substrate. The cold test methodology was adapted using three different temperatures (10°C, 5°C and 2°C), where each of the three temperatures was subjected to three exposure times (7 days, 3 days, 1 day). It was found that the different cold test methodologies studied differed in their ability to assess the vigor of maize seeds. The use of the paper roll proved to be appropriate for stratifying seed lots, as it allows for the separation of vigor levels with less use of manpower, shorter execution time, as well as taking up less space.